Elimination of murine and human T-cell epitopes in recombinant immunotoxin eliminates neutralizing and anti-drug antibodies in vivo - Mazor, Ronit (Cell Mol Immunol, 2017)
Antibodies against the toxin portion of recombinant immunotoxins (RIT) reduce their efficacy and pose a potential safety risk. To overcome this problem we mutated the very immunogenic immunotoxin SS1P to produce LMB-T20, a de-immunized RIT that has the eight human T-cell epitopes in SS1P modified or removed. To determine the effect of T-cell epitope removal in vivo we mapped the T-cell epitopes in immune-competent BALB/c mice and found that these mice recognize two epitopes. One corresponds to the human immunodominant T-cell epitope and the other to a human subdominant epitope; both were eliminated in LMB-T20. We found that mice immunized with LMB-T20 did not have T-cell activation and did not develop anti-drug antibodies (ADA), whereas mice immunized with SS1P, showed T-cell activation, and developed ADA detected by both ELISA and drug neutralizing assays. The ability of the mice treated with LMB-T20 to respond to other antigens was not compromised. We conclude that elimination of T-cell epitopes is sufficient to prevent formation of antibodies to an immunogenic foreign protein.